2012
DOI: 10.1061/(asce)wr.1943-5452.0000216
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Climate Change on Irrigated Agriculture in the Maipo Basin, Chile: Reliability of Water Rights and Changes in the Demand for Irrigation

Abstract: Agricultural regions located in snowmelt-dominated Mediterranean climate basins have been identified as being highly vulnerable to the impacts of climate change. The Maipo basin in central Chile is one such region. Projections of future climate conditions suggest major challenges for this basin. Precipitation levels are projected to decrease by the end of the century, and temperature levels in the mountains are expected to increase by around 3-4°C. Such changes would affect both river discharge and irrigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(60 citation statements)
references
References 24 publications
4
53
0
3
Order By: Relevance
“…Droughts have a profound effect on agricultural production and, therefore, were one of the greatest concerns expressed by participants of the workshops. The former is consistent with the study by Meza et al [42] and Vicuña et al [43], who found that the potential negative impact on crop production is sensitive to high seasonal water demand in Chile, which in turn is influenced by climate change-induced drought. A more optimistic interpretation is presented in the models developed by [44], on the basis of which the author foresees no harm to production potential in the southern regions, given the possibility of a general adaptive strategy based, for example, on implementing earlier planting dates to capture winter rains.…”
Section: How Are Droughts Experienced In Chile? System Knowledge (A)supporting
confidence: 81%
See 1 more Smart Citation
“…Droughts have a profound effect on agricultural production and, therefore, were one of the greatest concerns expressed by participants of the workshops. The former is consistent with the study by Meza et al [42] and Vicuña et al [43], who found that the potential negative impact on crop production is sensitive to high seasonal water demand in Chile, which in turn is influenced by climate change-induced drought. A more optimistic interpretation is presented in the models developed by [44], on the basis of which the author foresees no harm to production potential in the southern regions, given the possibility of a general adaptive strategy based, for example, on implementing earlier planting dates to capture winter rains.…”
Section: How Are Droughts Experienced In Chile? System Knowledge (A)supporting
confidence: 81%
“…First, the results emphasize the need to generate more information on, and raise awareness of, the causes and effects of drought, as well as the vulnerability of social and ecological systems. Second, participants mentioned a need for community adaptation through different practices, which is consistent not only with research findings on this topic in various regions of the country [42,47], but also with a series of concrete experiences of communities supported by international organizations and national NGOs [48,49]. Third, participants mentioned the need to improve institutional responses, in particular in relation to the adjustment of norms and regulations and the creation of flexible yet specific public policies.…”
Section: Types Of Impacts Región Del Bío Bío Región De Los Ríos Regiósupporting
confidence: 51%
“…Hydropower generation on the Tinguiririca River at La Higuera and La Confluencia (Pelto, 2011) will be affected by interannual variability in water supply and future streamflow trends in the medium to long term. Finally, more long-term highelevation stations in the Andes are necessary to establish the interannual variability of glacier contribution to river discharge in order to help manage future water availability, considering climate change and the increasing demand for water in the region (Meza et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…This region, incorporating the capital city, Santiago, has more than 10 million inhabitants representing 60 % of the country's population. In addition to domestic supply, water is a crucial resource for agriculture irrigation, industries, mining, hydropower generation, tourism and transport (Aitken et al, 2016;Masiokas et al, 2006;Meza et al, 2012;Ayala et al, 2016;Valdés-Pineda et al, 2014). Population growth and urban expansion in recent years have increased the demographic pressure on water resources (Meza et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Among the many factors, precipitation which is regarded as stochastic is an uncertain factor influencing irrigation (Wisser et al, 2008;Thomas, 2008;Cai et al, 2011;Meza et al, 2012). In general, the more precipitation is, the less water demand of irrigation is, and vice versa.…”
Section: Introductionmentioning
confidence: 99%